Synthesis and Hypolipidemic Activity of New 6,6-Disubstituted 3-R-6,7-Dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-Ones - Voskoboynik, О. Yu.; Kolomoets, O. S.; Antypenko, O. M.; Zhernova, G. О.; Nosulenko, I. S.; Berest, G. G.; Shvets, V. M.; Kovalenko, S. I.; Воскобойнік, Олексій Юрійович; Коломоєць, Олександра Сергіївна; Антипенко, Олексій Миколайович; Жернова, Галина Олександрівна; et al. (Wiley Periodicals, Inc., 2018)
Presented article describes the synthesis and hypolipidemic activity of previously unknown 6,6-disubstituted 3-R-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones. It was shown, that interaction of 6-R-3-(2-aminophenyl)-1,2,4-triazin-5(2Н)-оnes with methylalkylketones in acetic acid resulted the single product, namely, the desired tricyclic derivatives. At the same time, after refluxing of 6-R-3-(2-aminophenyl)-1,2,4-triazin-5(2Н)-оnes with methylarylketones in acetic acid the mixture of target compound and insignificant amount of corresponding 3-substituted 6-methyl-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones were isolated. The mechanism of above-mentioned mixture formation was discussed. The structures of all synthesized compounds were proven using the appropriate physicochemical methods. The compounds with promising lipid-lowering activity were identified and the «structure — hypolipidemic activity» correlations were discussed.